The Influence of Sustainability Report Disclosure and Environmental Performance on Company Financial Performance - Ria Andriani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the influence of sustainability report disclosure and environmental performance on company financial performance. As environmental concerns and corporate social responsibility gain importance, companies are increasingly expected to demonstrate accountability through transparent reporting and sustainable practices. The research employs a quantitative approach using secondary data from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange. Financial performance is measured using indicators such as Return on Assets (ROA) and Return on Equity (ROE), while environmental performance is assessed based on PROPER ratings. The findings indicate that both sustainability report disclosure and environmental performance have a significant and positive impact on the financial performance of companies. This suggests that companies that are more transparent in disclosing sustainability practices and perform well environmentally tend to gain higher trust from stakeholders, which contributes to improved financial outcomes.